Residents' perception toward protected areas - Carska Bara Special Nature Reserve (Vojvodina, Serbia) - Jojić Glavonjić, Tamara Miljan; Brankov, Jovana Jovan; Miljanović, Dragana (Geographica Pannonica, 2018)
The research was carried out in the villages of the buffer zone and the close environment of the Ramsar site “Stari Begej – Carska Bara” Special Nature Reserve, in the Serbian part of Banat. The survey method was used to establish the local population’s attitude towards the impact of area protection on their life quality and the degree of cooperation with the managing body. A total of 393 adults were surveyed, which accounted for 5.34% of the total adult population of the studied area (five villages). In order to provide opinions from all stakeholders, the managing body was also asked to respond to some of the questions. A comparison of the responses revealed a generally low level of dialogue and understanding between the two interested parties. The results indicate some differences in the degree of impact depending on the location of the villages, as well as the occupation of the respondents and their age.
Keywords: protected area; Ramsar; managing; attitude towards the impact; Serbia